The Role of SwrA, DegU and P(D3) in fla/che Expression in B. subtilis - Mordini, Serena (Public Library of Science, 2013)

(untitled)
In B. subtilis swarming and robust swimming motility require the positive trigger of SwrA on fla/che operon expression. Despite having an essential and specific activity, how SwrA executes this task has remained elusive thus far. We demonstrate here that SwrA acts at the main σ(A)-dependent fla/che promoter P(A(fla/che)) through DegU. Electrophoretic mobility shift assays (EMSA) reveal that SwrA forms a complex with the phosphorylated form of DegU (DegU~P) at P(A(fla/che)) while it is unable to do so with either unphosphorylated DegU or the DegU32(Hy) mutant protein. Motility assays show that a highly phosphorylated DegU is not detrimental for flagellar motility provided that SwrA is present; however, DegU~P represses P(A(fla/che)) in the absence of SwrA. Overall, our data support a model in which DegU~P is a dual regulator, acting either as a repressor when alone or as a positive regulator of P(A(fla/che)) when combined with SwrA. Finally, we demonstrate that the σ(D)-dependent P(D3(fla/che)) promoter plays an important role in motility, representing a contingent feedback loop necessary to maintain basal motility when swrA is switched to the non-functional swrA (-) status.